MEMBANGUN IDENTITAS YANG KUAT: MEMANFAATKAN PERSONAL BRANDING UNTUK MEMPERLUAS PASAR BAGI UMKM DISABILITAS: DI GRAHA NAWASENA DENPASAR - Purwaningrat, Putu Atim; Suputra, Gusti Alit; Adisti A W, Ni Luh; Surya D, Gde Indra; Agus W, I Wayan; Agus Y P, I Putu (Dharma Bhakti, 2024)
Barriers to mobility and accessibility are the main factors for people with disabilities in carrying out economic activities. Graha Nawasena House of Hope for Disabilities, Denpasar City, Bali was established to facilitate people with disabilities so they can continue to innovate and inspire their entrepreneurial spirit. In general, this Community Service activity aims to solve problems as well as provide solutions to social and economic problems that occur in society, especially for people with disabilities at Graha Nawasena Denpasar. The aim of this Community Service activity is to develop self-confidence and branding; Optimizing the use of technology; Increasing market accessibility; Promote inclusion and equality